HEGEMONI DALAM NOVEL GADIS PANTAI KARYA PRAMOEDYA ANANTA TOER KAJIAN ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH - A. Fitriah; Idris; Irna Fitriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explain the discourse structure of the novel Gadis Pantai by Pramoedya Ananta Toer in representing hegemonic practices through linguistic aspects. The primary focus is on text-level analysis within Norman Fairclough’s critical discourse analysis framework. The research employs a descriptive qualitative method, with primary data consisting of narrative and dialogue excerpts that reflect power relations, particularly those related to social class and gender. Secondary data are drawn from relevant theoretical sources to support the analysis. Data were collected through documentation using reading and note-taking techniques, while data analysis was concentrated on the textual dimension of Fairclough’s model. The researcher served as the main instrument, supported by theoretical triangulation to ensure data validity. The findings indicate that the discourse structure at the textual level reveals the use of descriptive diction rich in ideological meaning. Lexical relations and contrasts are employed to emphasize differences in social positions among characters. In addition, the use of fragmentary sentences reflects the psychological pressure and power imbalance experienced by the main character. Cohesion and coherence also play a crucial role in constructing a consistent discourse that represents dominance by certain groups. Overall, the linguistic structure in the novel functions not only as a means of communication but also as an ideological tool to reproduce and reinforce hegemonic practices within a particular social context.